Pengaruh Strategi Pemecahan Masalah Wankat dan Oreovocz Terhadap Kemampuan Kognitif Pada Konsep Hukum Newton dan Penerapannya - Rachmawati, Rachmawati (Jurnal Gemaedu, 2018)
: This study aims to determine the effect of Wankat and Oreovocz problem solving strategies on cognitive abilities in Newton's legal concepts and their application. This research was conducted at the State High School 08 in Bogor City. In this study, the experimental class was class X MIA 2, while the control class was class X MIA 1. Determination of the sample in this study was based on purposive sampling technique. The research method used is a quasi-experimental method. The study took place in the first semester of the 2015-2016 school year. The instrument used is a test instrument in the form of a subjective test. Based on test data analysis, it was concluded that there was an influence of Wankat and Oreovocz's problem solving strategies on cognitive abilities in Newton's legal concepts and their application. This is based on the results of hypothesis testing using the t-test for N = 31 for the posttest data. Sig. (2-tailed) value is 0.001, while the significance value is 0.05 or Sig. (2-tailed) <0.05